Application of Fobio Biopesticide in Suppressing the Intensity of Bacterial Leaf Blight Disease in Paddy Plants Using Integrated Pest Management (IPM) in Rice Fields of Puton Village, Diwek District, Jombang Regency, East Java - Haykal, Arkan; Wiyatiningsih, Sri; Purnawati, Arika (Eduvest - Journal of Universal Studies, 2025)
Control of bacterial leaf blight in rice plants is often done by applying chemical pesticides whose future effects will be very bad for the soil and plants that will be planted next. An alternative that can be applied is using the biopesticide Fobio. The aim of this research was to measure the effectiveness of the application of fobio in reducing the intensity of bacterial leaf blight attacks. This research was carried out in June-September 2023 in Diwek District, Jombang Regency. The study used a Randomized Block Design with two factors, namely the Fobio dose consisting of 3 levels, namely P0 (without giving Fobio / 0ml/liter), P5 (dose 5 ml/liter), and P10 (dose 10 ml/liter), the second factor was long The soaking time for seeds using Fobio consists of 3 levels, namely W10 (10 minutes soaking time), W20 (20 minutes soaking time), and W30 (30 minutes soaking time) so there are 9 treatment combinations. Observation parameters include plant height, number of leaves, number of tillers, and intensity of disease attacks. The results of the combination treatment were not significantly different for the number of leaves and number of tillers, for single and combination treatments the plant height and intensity of disease attacks were significantly different. Application of Fobio can increase plant height, number of leaves, and number of tillers on rice plants, and Fobio can suppress bacterial leaf blight attacks that attack rice plants.